The Effect of Clinical Leadership of the Head of the Room on Nurse Satisfaction in the Internal Room at Toto Kabila Hospital - Riskawaty Lihawa; Sabirin B. Syukur; Euis Herawati Hidayat (Universitas Muhammadiyah Palu, 2026)
Hospitals are one of the means of health services that are expected to provide the best service for individuals and the community in accordance with the vision and mission set. This study aims to identify the influence of clinical leadership of the head of the room on nurse satisfaction at Toto Kabila Hospital. This study uses a correlational approach with a cross-sectional design. The population in this study is all implementing nurses in the internal room of Toto Kabila Hospital with a non-probability sampling technique of total sampling method, so that the total sample number is 36 people. Data analysis used chi-square statistical tests. The results showed that as many as 30 respondents (84.2%) were in the good category of clinical leadership and 6 respondents (15.8%) were in the adequate category. Nurse satisfaction is measured based on five dimensions, namely reward and support, supervisor communication, division of duties, work environment, and self-development opportunities. The results of the satisfaction assessment showed that as many as 31 respondents (86.8%) were in the satisfied category and 5 respondents (13.2%) were in the dissatisfied category. The results of the chi-square test analysis showed a value of p=0.000 < (0.05). The conclusion of this study is that there is an influence of the clinical leadership of the head of the room on the satisfaction of nurses in the Internal Room of Toto Kabila Hospital. It is hoped that this research can be the basis for hospitals to design policies or programs that focus on developing clinical leadership for room heads.